Translating disability towards social justice: Turning representations of persons with disabilities upside DOWN - Taviano, Stefania (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2024)
Disability activism, together with social, gender, and racial justice struggles, has gained increased visibility in both civil society and academia. As a translation scholar and as the mother of an 11-year-old boy with Down syndrome engaged in promoting social justice, I strive to challenge the predominant representations of persons with disabilities that prevent them from exercising their human rights. This article proposes to build on the interdisciplinary intersections between feminist disability studies and critical translation studies, including audiovisual translation and media accessibility. It does so with a view to accounting for and contributing to inclusive practices in the translation of disability; it does so also to challenge ableist re-translation in a world where much remains to be done to protect the human rights of people with disabilities. The article analyses the political translation of disability in a video campaign carried out by the National Coordination of Associations of Persons with Down Syndrome (CoorDown). Released on the 2021 World Down Syndrome Day, the video titled Dear Future Mom is a collective response to an expectant mother of a child with Down syndrome who wrote to Coordown to share her uncertainties and fears following the diagnosis of Down syndrome. Including multiple languages and featuring children with Down syndrome as the main protagonists, Dear Future Mom creates a translational political space where the binary oppositions between non-disabled and disabled people are subverted. The video performs a political translation of the “original” textual body of children and young adults with disabilities that frames disability as compatible with a fulfilled life. The social model of disability that informs this political translation is challenged by the social and legal controversies surrounding the reception of the video. In criticizing the medical model of disability and its conflation of “defective bodies” with defective lives, this article alerts readers to the human rights consequences of this model for persons with disabilities and calls for alternative political translations that align themselves with disability activism and social justice struggles.